Human precision-cut liver slices as a model to test antifibrotic drugs in the early onset of liver fibrosis. (September 2016) - Westra, Inge M.; Mutsaers, Henricus A.M.; Luangmonkong, Theerut; Hadi, Mackenzie; Oosterhuis, Dorenda; de Jong, Koert P.; Groothuis, Geny M.M.; Olinga, Peter
Abstract: Liver fibrosis is the progressive accumulation of connective tissue ultimately resulting in loss of organ function. Currently, no effective antifibrotics are available due to a lack of reliable human models. Here we investigated the fibrotic process in human precision-cut liver slices (PCLS) and studied the efficacy of multiple putative antifibrotic compounds. Our results demonstrated that human PCLS remained viable for 48 h and the early onset of fibrosis was observed during culture, as demonstrated by an increased gene expression of Heat Shock Protein 47 (HSP47) and Pro-Collagen 1A1 (PCOL1A1) as well as increased collagen 1 protein levels. SB203580, a specific inhibitor of p38 mitogen-activated protein kinase (MAPK) showed a marked decrease in HSP47 and PCOL1A1 gene expression, whereas specific inhibitors of Smad 3 and Rac-1 showed no or only minor effects. Regarding the studied antifibrotics, gene levels of HSP47 and PCOL1A1 could be down-regulated with sunitinib and valproic acid, while PCOL1A1 expression was reduced following treatment with rosmarinic acid, tetrandrine and pirfenidone. These results are in contrast with prior data obtained in rat PCLS, indicating that antifibrotic drug efficacy is clearly species-specific. Thus, human PCLS is a promising model for liver fibrosis. Moreover, MAPK signaling plays an important role in the onset of fibrosis in this model and transforming growth factor beta pathway inhibitors appear to be more effective than platelet-derived growth factor pathway inhibitors in halting fibrogenesis in PCLS. Highlights: Human precision-cut liver slices (PCLS) is a good in vitro model to study fibrosis. Early onset of fibrosis during culture of human PCLS P38 MAPK pathway most important for fibrogenesis in human PCLS TGF-β-inhibitors more effective as antifibrotic drugs than PDGF-inhibitors